2022
DOI: 10.1038/s41467-022-29086-x
|View full text |Cite
|
Sign up to set email alerts
|

Growing single crystals of two-dimensional covalent organic frameworks enabled by intermediate tracing study

Abstract: Resolving single-crystal structures of two-dimensional covalent organic frameworks (2D COFs) is a great challenge, hindered in part by limited strategies for growing high-quality crystals. A better understanding of the growth mechanism facilitates development of methods to grow high-quality 2D COF single crystals. Here, we take a different perspective to explore the 2D COF growth process by tracing growth intermediates. We discover two different growth mechanisms, nucleation and self-healing, in which self-ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
114
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 47 publications
0
114
1
Order By: Relevance
“…This 2D polymer had been reported previously as a polycrystalline powder by Bein and coworkers under traditional solvothermal conditions and reaction times of 1–3 days . Zhao and coworkers subsequently reported micron-sized single crystals of the same COF, which were obtained solvothermally using reaction times of 1–3 months . These early examples of high-quality imine-linked 2D COFs inspire our present work, which focuses on conditions that provide 2D COFs of comparable quality, ideally without requiring high pressure reactors or extended reaction times.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…This 2D polymer had been reported previously as a polycrystalline powder by Bein and coworkers under traditional solvothermal conditions and reaction times of 1–3 days . Zhao and coworkers subsequently reported micron-sized single crystals of the same COF, which were obtained solvothermally using reaction times of 1–3 months . These early examples of high-quality imine-linked 2D COFs inspire our present work, which focuses on conditions that provide 2D COFs of comparable quality, ideally without requiring high pressure reactors or extended reaction times.…”
Section: Introductionmentioning
confidence: 57%
“…Deng and coworkers also proposed an offset mode through scanning transmission electron microscopy (STEM) and the ratio of intensities of the 130 and 040 reflections in the PXRD patterns . In the recent report of the TAPPy-PDA COF single crystals synthesized by Zhao and coworkers, only about 10% of the crystals adopt a fully eclipsed structure, whereas almost 90% of the crystals adopt a structure containing 6 different stacking layers within the unit cell . In general, the disordered stacking in 2D COFs is the primary reason their crystal structures cannot be solved directly even when their individual 2D polymer sheets are single crystals with micron-scale lateral dimensions.…”
Section: Resultsmentioning
confidence: 99%
“…The mixture of polar and nonpolar solvents (like mesitylene : dioxane; o -dichlorobenzene : n -butanol) facilitates the prearrangement of the monomers and oligomers, and thus regulates their self-assembly process. 70 Dichtel and coworkers revealed that the systematic addition of increasing amounts of water to the reaction mixture facilitated the backward reaction in COFs, thereby improving the crystallisation process of COFs. 59 On the other hand, metal-catalysed polymerisation of amorphous POPs (CMPs, PAFs) typically proceeds through the formation of oligomers at the initial stage.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it is important to note that current characterization techniques are incapable of unambiguously determining the chemical purity, stacking pattern, crystal domain size, defect density, and many other structural features of COFs. 86,[869][870][871][872] Each of these features with uncertainties may impact the interaction of metal ions with COFs, which further complicates the structure-property relationships of metalated COFs. Theoretical calculations are powerful tools for studying the structure and properties of materials; for example, first-principles calculations, molecular dynamics simulations, and grand canonical Monte Carlo simulations have been applied in the study of the binding sites of light metals in COFs, 402 optimization of the unit cell structure of COFs, 852 prediction of gas adsorption behaviors, 412,873,874 and design and screening of electrocatalysts.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is important to note that current characterization techniques are incapable of unambiguously determining the chemical purity, stacking pattern, crystal domain size, defect density, and many other structural features of COFs. 86,869–872 Each of these features with uncertainties may impact the interaction of metal ions with COFs, which further complicates the structure–property relationships of metalated COFs.…”
Section: Discussionmentioning
confidence: 99%